2013
DOI: 10.1093/neuonc/nos308
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of O6-methylguanine-DNA methyltransferase protein expression and promoter methylation provides optimized prognostication of glioblastoma outcome

Abstract: Optimal assessment of MGMT status as a prognostic biomarker for patients with newly diagnosed GBM treated with chemoradiation requires determination of both promoter methylation and IHC protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 44 publications
9
91
0
5
Order By: Relevance
“…For example, MGMT promoter methylation status was found to be promising prognostic biomarker in patients with glioblastoma multiforme (GBM) treated with radiation and TMZ, as methylated patients demonstrated a median overall survival (OS) of 24.7 months, whereas unmethylated patients demonstrated a median OS of 16.2 months. Progression free survival (PFS) was also higher among methylated than among unmethylated patients (13.3 months vs. 7.8 months) [95]. This is in agreement with results of another study that showed MGMT methylation was correlated with better survival of treated GBM patients with a hazard ratio (HR) of 0.61 [96].…”
Section: Dna Repair Gene Methylation Status As Biomarkersupporting
confidence: 86%
“…For example, MGMT promoter methylation status was found to be promising prognostic biomarker in patients with glioblastoma multiforme (GBM) treated with radiation and TMZ, as methylated patients demonstrated a median overall survival (OS) of 24.7 months, whereas unmethylated patients demonstrated a median OS of 16.2 months. Progression free survival (PFS) was also higher among methylated than among unmethylated patients (13.3 months vs. 7.8 months) [95]. This is in agreement with results of another study that showed MGMT methylation was correlated with better survival of treated GBM patients with a hazard ratio (HR) of 0.61 [96].…”
Section: Dna Repair Gene Methylation Status As Biomarkersupporting
confidence: 86%
“…To date, only one study has specifically used a cohort of patients who received chemoradiotherapy. Lalezari et al (24) reported that their analysis of 418 patients with GBM, including 410 who received chemoradiotherapy with TMZ, indicated that MGMT status, gender, age, KPS score, resection and IDH1 mutations Figure 1. Kaplan-Meier curve of overall survival (A) and progression-free survival (B) in isocitrate dehydrogenase 1/2 (IDH1/2) mutant and IDH1/2 wild-type glioblastoma (GBM) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MGMT promoter status alone might not be sufficient as marker in a clinical setting. As already described for glioblastoma and NET tumors, we propose that this issue could be overcome by combining promoter methylation with IHC (47,48).…”
Section: /Mgmtmentioning
confidence: 94%